The Influence of Taxation Knowledge, Socialization, and Attitudes Required on Individual Taxpayer Compliance in Tambun Selatan District, Bekasi Regency - Rachmawati; Mulyadi, Mulyadi; Hasanudin, Hasannudin (Business and Entrepreneurial Review, 2023)
This study aims to study how knowledge about taxation, socialization about taxation, and individual taxpayers' attitudes impact the level of compliance in South Tambun Regency, West Java Province. This study applies a quantitative descriptive approach. The SPSS version 25 application was used to analyze the data. This study had many respondents, 186,411, but only 100 samples were selected using the Slovin formula. All taxpayers with a Taxpayer Identification Number (NPWP) and individual SPT are selected purposively. The results regarding tax knowledge show that tax knowledge significantly impacts the level of compliance of individual taxpayers in the Tambun District. The calculated t value is smaller than the critical value showing this fact.